Reine Vermögensschäden im Europäischen Internationalen Deliktsrecht. Zuständigkeit und anwendbares Recht. - Meyle, Hannes (Schriften zum Internationalen Recht, 2021)
In private international law, localisation of cross-border torts that result in pure economic loss is unpredictable. Both jurisdiction and applicable law are dominated by case-by-case decisions. The problem already existed at the time of the German Reichsgericht and it has not been solved by the ECJ yet. The thesis shows why the place of damage is an unsuitable connecting factor for pure economic loss cases and develops reform proposals.